The European lactase persistence genotype determines the lactase persistence state and correlates with gastrointestinal symptoms in the Hispanic and Amerindian Chilean population: a case–control and population-based study. Issue 1 (29th July 2011) - Morales, Eugenia; Azocar, Lorena; Maul, Ximena; Perez, Claudio; Chianale, José; Miquel, Juan Francisco
Abstract : Background: The lactase persistent (LP) or lactase non-persistent (LNP) state in European adults is genetically determined by a single nucleotide polymorphism (SNP) located 13.9 kb upstream of the lactase (LCT) gene, known as LCT C>T−13910 (rs4988235). The LNP condition leads to an inability to digest the milk sugar lactose leading to gastrointestinal symptoms and can affect nutrient and calcium intake in certain populations. Objectives: The authors studied a group of 51 Chilean patients to assess whether this SNP influences the LP/LNP state in this population, and determined the prevalence of LCT C>T−13910 genotypes in a representative sample of 216 Hispanics and 43 Amerindians with correlation to digestive symptoms. Design: Case–control study done in Chilean patients with clinical suspicion of LNP that were assessed using clinical survey, hydrogen breath test (HBT) and SNP genotyping. The population sample of Hispanics and Amerindians was assessed by clinical survey and SNP genotyping. Results: Of the 51 patients with clinical suspicion of LNP, 29 were HBT-positive. The CC genotype (LNP) was present in 89.7% of the patients with positive HBT and in only 4.7% of those with negative HBT. The prevalence of the CC genotype was 56.9% in the Hispanic population and 88.3% in Amerindians, and was associated with a higher self-reported clinical intolerance to ingestion of dairy products. Conclusion: The LP/LNP state is determined by the LCT C>T−13910 variant in Chileans. This variant predicts digestive symptoms associated with the ingestion of lactose and is a good tool for the diagnosis of primary adult hypolactasia. The LCT T−13910 allele is rare in the Amerindian population and is suggestive of European ancestry in this contemporary population.